2010
DOI: 10.1523/jneurosci.5319-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Autocoherence in the Cortical Network with a Time-Frequency Analysis of the Local Field Potential

Abstract: Gamma-band peaks in the power spectrum of local field potentials (LFP) are found in multiple brain regions. It has been theorized that gamma oscillations may serve as a 'clock' signal for the purposes of precise temporal encoding of information and 'binding' of stimulus features across regions of the brain. Neurons in model networks may exhibit periodic spike firing or synchronized membrane potentials that give rise to a gamma-band oscillation that could operate as a 'clock.' The phase of the oscillation in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 74 publications
10
90
0
Order By: Relevance
“…Combined with these results, our findings support the idea that gamma rhythms are a resonant phenomenon arising from the interaction between local excitation and inhibition (Atallah and Scanziani, 2009; Brunel and Wang, 2003; Kang et al, 2009; Burns et al, 2010). Several fundamental cortical mechanisms such as divisive normalization (Heeger, 1992), adaptation (Heiss et al, 2008; Higley and Contreras, 2006) and gain control (Chance et al, 2002; Shu et al, 2003) rely on excitatory-inhibitory interactions; thus it is not surprising that detectable gamma rhythm is also present and is modulated during a variety of cognitive tasks such as attention (Fries et al, 2001; Womelsdorf and Fries, 2007), working memory (Pesaran et al, 2002) or cortico-spinal interactions (Schoffelen et al, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Combined with these results, our findings support the idea that gamma rhythms are a resonant phenomenon arising from the interaction between local excitation and inhibition (Atallah and Scanziani, 2009; Brunel and Wang, 2003; Kang et al, 2009; Burns et al, 2010). Several fundamental cortical mechanisms such as divisive normalization (Heeger, 1992), adaptation (Heiss et al, 2008; Higley and Contreras, 2006) and gain control (Chance et al, 2002; Shu et al, 2003) rely on excitatory-inhibitory interactions; thus it is not surprising that detectable gamma rhythm is also present and is modulated during a variety of cognitive tasks such as attention (Fries et al, 2001; Womelsdorf and Fries, 2007), working memory (Pesaran et al, 2002) or cortico-spinal interactions (Schoffelen et al, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Such a moment of disorder creates the prerequisites for a stimulus to induce a reorganization of the background activity and to prompt the emergence of the subsequent attractor (Freeman, 2004(Freeman, , 2009). These results imply that noise plays a fundamental role in the functioning of the brain, which has been confirmed by investigations of other groups (Kitajo, Doesburg, Yamanaka, Nozaki, Ward, & Yamamoto, 2007;Burns, Xing, Shelley, & Shapley, 2010;Burns, Xing, & Shapley, 2011).…”
Section: Realization Of the Mechanism In The Brainsupporting
confidence: 80%
“…Finally, recent studies that have looked at the reliability and consistency of gamma rhythms have reported that gamma is highly stochastic and lacks the attributes necessary to provide a clock or a communication channel (Figure 2e) [6365]. Although part of this stochasticity could be due to changes in the behavioural state of the animal or variability associated with the estimation of power, and the proposed mechanisms could potentially operate even when gamma is not a perfect clocking signal [66], these mechanisms still require gamma to have enough power to generate time epochs in which the neurons are sufficiently depolarized to temporally coordinate their firing.…”
Section: Low and Inconsistent Powermentioning
confidence: 99%